CRITICAL PATH METHOD (CPM) APPLICATION IN TIME MANAGEMENT OF THE MALAKA REGENCY OFFICE BUILDING PROJECT - Seki, Thomas Aquino; Patriadi, Andi; Sajiyo, Sajiyo (International Journal of Social Service and Research, 2025)
The construction of the Malaka Regency Regent's Office has faced significant challenges, including frequent delays in project completion due to various factors such as design changes, unpredictable weather conditions, labor shortages, and inadequate materials or equipment. These issues have led to inefficiencies in time and cost management, emphasizing the need for effective project management strategies. This study applies the Critical Path Method (CPM) to analyze the project timeline, identify the critical path, and propose measures for project acceleration. By employing CPM, the project schedule was meticulously reviewed and optimized, resulting in a reduction of the initial planned duration from 180 calendar days to 100 calendar days. This acceleration was achieved by minimizing lag times between critical activities, reallocating resources, and implementing time-cost trade-off strategies, all without compromising the quality or scope of the project deliverables. The results demonstrate the effectiveness of CPM in streamlining construction project timelines and mitigating delays. Additionally, this study provides a practical framework for addressing time and cost overruns in construction projects, particularly in the context of public infrastructure development. By highlighting the integration of project management tools like CPM, this research contributes to the broader understanding of efficient scheduling practices and offers actionable insights for similar projects in the future.